2022
DOI: 10.1097/mcp.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and real-life experience in progressive pulmonary fibrosis

Abstract: Purpose of reviewIdiopathic pulmonary fibrosis (IPF), characterized by relentless disease progression from the time of diagnosis, is part of a larger group of chronic fibrosing interstitial lung diseases (ILDs). A proportion of patients with non-IPF ILDs may develop, despite conventional treatment, a progressive pulmonary fibrosis (PPF), also referred to as ILD with a progressive fibrosing phenotype (PF-ILD). These patients experience worsening of respiratory symptoms, decline in lung function, and early morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
2
8
0
4
Order By: Relevance
“…[5,9,19] The prevalence of PPF has been reported to vary widely in previous studies, ranging from 14.5% to 47.5%. [20] Generally, it has been reported to be approximately 30%, similar to the results reported by Wijsenbeek et al (up to 32%) [1] and Nasser et al (27.2%). [17] The proportion of PPF in patients with ILD other than IPF in our study was higher than that reported previously.…”
Section: Discussionsupporting
confidence: 83%
“…[5,9,19] The prevalence of PPF has been reported to vary widely in previous studies, ranging from 14.5% to 47.5%. [20] Generally, it has been reported to be approximately 30%, similar to the results reported by Wijsenbeek et al (up to 32%) [1] and Nasser et al (27.2%). [17] The proportion of PPF in patients with ILD other than IPF in our study was higher than that reported previously.…”
Section: Discussionsupporting
confidence: 83%
“…IPF was diagnosed in accordance with international and national guidelines [ 2 , 3 , 25 , 28 ]. In patients with a high clinical probability of IPF, and HRCT pattern not consistent with UIP, in whom a biopsy was not available, a working diagnosis of IPF was made [ 8 ]. Unclassifiable idiopathic interstitial pneumonia (IIP) was defined as the absence of a confident diagnosis, using an MDD as the standard for ILDs diagnosis [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, two antifibrotic drugs, pirfenidone and nintedanib, have been approved for the treatment of IPF based on large randomized clinical trials [ 4 , 5 , 6 , 7 ]. In addition to conducting clinical trials to evaluate the efficacy and safety of new treatments, observational studies from real clinical practice are also needed to understand the natural course of the disease and patients’ responses to therapy [ 8 ]. Data from real patient registries may be more representative of clinical practice than results from clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…ILD is a growing global health issue, with an increase of 86% in ILD-related mortality ( 92 , 93 ) and predicted to account for 0.26% of all-cause mortality in 2027 in the world A recent study found that the prevalence of ILD ranged from 6.3 to 71 per 100,000 people, and the incidence rate of ILD ranged from 1 to 31.5 per 100,000 people per year ( 94 ). Another study from France reported a prevalence rate of 97.9 per 100,000 and incidence of 19.4 per 100,000 for individual per year ( 95 ).…”
Section: Epidemiologymentioning
confidence: 99%